THE ANALYSIS OF THE ACHIEVEMENT OF READING COMPREHENSION BY THE STUDENTS IN THE REPORT TEXT AT THE ELEVENTH GRADE SMK NURHASANAH MEDAN IN 2023: ANALISIS PRESTASI PEMAHAMAN BACAAN SISWA PADA TEKS LAPORAN KELAS XI SMK NURHASANAH MEDAN TAHUN 2023 - Aminah Hasibuan, Siti (UPMI Proceeding Series, 2023)
This objective of this study was to know the students’reading comprehension in the report text at the eleventh grade of SMK Nurhasanah Medan in academic year of 2023. Therefore the researcher formulated a problem statement: How is the students’ reading comprehension at the eleventh grade of SMK Nurhasanah Medan in academic year of 2023. This research was carried out at in May 2023. This research used qualitative analysis design. The population of the study was the eleventh grade of SMK Nurhasanah Medan in academic year of 2023. The total student in eleventh grade is 156 students. The samples of this research are 32 students. The researcher used documentation and interview in collecting the data. The documentation was used to take the data of the students’ results in reading comprehension in the report text, whereas the interview used to know the students’ level of reading comprehension. The technique used to analyze the data was using data reduction, the data representation/ display, and the drawing conclusion/ verification. From the analysis, based on the result of the data from the documentation and the interview, it could be concluded that the students in the eleventh grade of SMK Nurhasanah Medan in academic year of 2023 used some techniques when doing in reading text. The techniques used are using background knowledge, prediction, inferences, using dictionary, grammatical analysis and translation. Furthermore, for the component skills model of comprehension, the students were teaching by the DIME model. And the category/level reading comprehension in the Students’ Reading Comprehension in the Report Text at the Eleventh Grade SMK Nurhasanah Medan in Academic Year of 2023 is the literal reading comprehension.